Augmenting the Hadba Minaret Role as A Landmark in the city of Mosul - Alomary, Ahmed Yousif; Alqimaqche, Nahedh Taha; Alallaf, Emad Hani (Sulaimani Journal for Engineering Sciences, 2015)
Al-Hadba, the oblique Minaret of the historic Grand Mosque is considered as the famous and the most important landmark in the old town of Mosul as it is the oldest architectural monument which have been built in 568 AH – 1172 AC. Till now, as a visual landmark of 45 meters height, it is the icon that gives the city its identity across nine centuries, which represents as an obvious indicator for orienting the direction of inhabitants movements in the old built fabric from remote distance, and as a component of this environment, it is characterized as a vital value for the visual views those can be seen through alleys that lead to the Grand Mosque, consequently, presenting richness, continuity and variety for such visual scenes. As a result of disorder of urban built, random buildings, unconsidered planning decisions, and the lack of prior urban design dimension which gives the Minaret its importance to the surrounding areas of the mosque, all that led to reduce the Minaret role as an urban landmark, besides creating vision coverage that prevented the Minaret from being as a visual mark. This paper attempts to study all visual districts in Mosul city in which the Minaret currently can be seen through alleys, in any viewpoint, direction and skyline with determining the built constructions that cover or reduce the visual sight toward the Minaret, evaluating the extent and level of its perception as a landmark on pedestrians level, identifying the best visual positions in the sequence, and presenting urban recommendations about how to improve the Minaret role as a monumental landmark in the city.
Keywords: Visual perception; Urban landmarks; Mosul City; Al-Hadba Minaret